The Effect of Reading Interest on Spatial Ability in Eliv Assisted Geometry Learning - Destia Wahyu Hidayati; Arie Wahyuni (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2022)
Space and form are one of the contents of mathematical literacy in PISA, which is included in the learning of geometry material. Learning abstract geometry, especially spatial geometry, will be an obstacle in education, so spatial abilities are needed. However, before using spatial abilities to imagine space and form, it is necessary to have reading skills manifested in reading interest. Therefore, this research needs to be done to open the minds of readers and provide information that interest in reading affects spatial abilities, so that government policies on reading habituation at the beginning of learning time can be preserved and even improved through other activities. This study aimed to determine how reading interest affects the spatial ability and how much reading interest affects spatial ability. This research is quantitative. The research subjects were the Mathematics Education Study Program students at Ivet University. Data collection techniques used are tests and scales. The research instrument is a reading interest scale and spatial ability test questions. The data analysis technique used is the normality test and regression test. The results of this study are the influence of reading interest on spatial ability, and reading interest affects the spatial ability of 52.5%. Keywords: reading interest, spatial ability, geometry